On quasiconformal mappings corresponding to the beltrami equation - Samsoniya, Z. V.; Samkharadze, I. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
By using methods of integral equations, we investigate problems of conformal and quasiconformal mappings of close domains.